PENINGKATAN PENGUASAAN KONSEP SISWA MELALUI PEMBELAJARAN ARGUMENT DRIVEN INQUIRY PADA PEMBELAJARAN IPA TERPADU DI SMP KELAS VII - Yuli Andriani; Riandi Riandi (Faculty of Education and Teacher Training, UIN (State Islamic University) Syarif Hidayatul, 2015)
AbstractMastery of the concept of science which is still low in the schools is the joint work of practitioners of science education. Learning science should be based on the nature of science itself that is the process of investigating the nature around systematically, but it has not been done by the school because most of the learning is still in the form of direct transfer from teachers to students. Learning ADI (Argument Driven Inquiry) is seen to facilitate students to understand the concept of science as well. Research on the implementation of the ADI (Argument Driven Inquiry) to improve the mastery of concepts is done in junior high school students of class VII in one of the Junior High School in Garut district, with 66 students who were divided into two classes namely experimental class that implemented ADI (Argument Driven Inquiry) and the control class that used guided inquiry learning. The results showed Application Inquiry Driven Argument learning model can significantly improve students' mastery of concepts than learning with guided inquiry. The cognitive aspect which aspect is the most improved is C2 (understand) both in the classroom that uses the learning Argument Driven Inquiry as well as in the classroom using learning Inquiry guided, and mastery of concepts most improved is in matter convection either in class that used the learning Argument Driven Inquiry as well as in the classroom which used guided Inquiry learning. AbstrakPenguasaan konsep IPA yang masih rendah di sekolah-sekolah merupakan pekerjaan bersama dari praktisi pendidikan IPA. Pembelajaran IPA seharusnya dilakukan berdasarkan hakikat IPA itu sendiri yakni proses penyelidikan terhadap alam sekitar secara sistematis, namun hal ini belum banyak dilakukan oleh sekolah karena pembelajaran sebagian besar masih berupa transfer langsung dari guru pada siswa. Pembelajaran ADI (Argument Driven Inquiry) dipandang dapat memfasilitasi siswa untuk memahami konsep IPA secara baik. Penelitian mengenai implementasi ADI (Argument Driven Inquiry) dalam meningkatkan penguasaan konsep dilakukan pada siswa SMP kelas VII di salah satu SMP Negeri di kabupaten Garut terhadap 66 siswa yang dibagi ke dalam dua kelas yakni kelas eksperimen yang menerapkan ADI (Argument Driven Inquiry) dan kelas kontrol yang menggunakan pembelajaran inquiry terbimbing. Hasil penelitian menunjukan Penerapan model pembelajaran Argument Driven Inquiry secara signifikan dapat meningkatkan penguasaan konsep siswa dibandingkan pembelajaran dengan inquiry terbimbing. Aspek kognitif yang paling meningkat adalah aspek C2 (memahami) baik di kelas yang menggunakan pembelajaran Argument Driven Inquiry maupun di kelas yang menggunakan pembelajaran Inquiry terbimbing dan penguasaan konsep yang paling meningkat adalah pada materi konveksi baik di kelas yang menggunakan pembelajaran Argument Driven Inquiry maupun di kelas yang menggunakan pembelajaran Inquiry terbimbing.Permalink/DOI: http://dx.doi.org/10.15408/es.v7i2.1578